Hazards of Repeat Pregnancy during Adolescence: A Case-control Study - Rafael Bessa de Freitas Galvão; Camilla Olivares Figueira; Anderson Borovac-Pinheiro; Daiane Sofia de Morais Paulino; Debora Bicudo Faria-Schützer; Fernanda Garanhani Surita (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To evaluate the social, obstetric and psychological risk factors related to repeat pregnancy in teenagers. Methods A case control study conducted at Centro de Atenção à Saúde Integral da Mulher (Caism, in the Portuguese acronym), in Campinas, Brazil, from 2015 to 2017. Three groups were selected: a case-group of adolescents who had repeat pregnancy and two control-groups, one consisting of adolescents who had delivered at first time and another one of adult women with more than one deliveries. Participants were asked about habits, socio-demographics characteristics, reproductive and obstetric history and assessed psychological issues. Results Ninety women were enrolled, 30 in each study group. Adolescents with repeat pregnancy have lower self-esteem scores and more ineffective contraceptive use. When compared with teens at first delivery, they had less schooling level (odds ratio [OR] 4.03 [1.37-11.8]), more school abandon (OR 8.16 [2.36-28.2]) and drugs use (OR 4.97[1.39-17.8]). Non-white skin color (OR 6.2 [1.15-41.0]), drugs use (OR 17.5 [2.62-116.6]) and first sexual intercourse under 15y (OR 18.0[2.82-115.0]) were found as higher risk factors for repeat pregnancy when comparing adolescents and adults.Moreover, adolescents withmore than one gestation had lower self-esteem and greater susceptibility to unplanned pregnancy. Conclusion There was an association between repeat pregnancy among adolescents and lower education, early onset of sexual activity, non-white skin color, low use of contraception and increased use of drugs.